Development and mechanical evaluation of a new interlocking earth masonry block. Issue 2 (January 2020) - Ma, Hongwang; Ma, Qi; Gaire, Prakash
An innovative interlocking compressed earth block, called interlocking compressed earth block developed at Shanghai Jiao Tong University, was developed for structural masonry. The locking mechanism of the interlocking compressed earth block developed at Shanghai Jiao Tong University completely depends on the grout in the vertical holes. Therefore, there is no gap between the interlocking key and the blocks, which increases the wall stability and reduces the block manufacturing costs. Experimental studies on the mechanical behavior of the unit (the block) and the masonry (prism constructed with a dry interface) were performed in accordance with the related standards. Soil samples from the northern Gansu Province of China were collected and studied. Small cylindrical samples were tested to determine the compressive and splitting tensile strength. Subsequently, the compressive strength of the prisms with three dry-stack blocks and the shear behavior of the masonry through the triplet test were investigated. The results show that the compressive and shear strengths meet the related standards. This work may provide a valuable structural system for low-cost, eco-friendly dwelling in developing countries.